If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(t + -7) + -7(2t + 1) = -17 Reorder the terms: -8(-7 + t) + -7(2t + 1) = -17 (-7 * -8 + t * -8) + -7(2t + 1) = -17 (56 + -8t) + -7(2t + 1) = -17 Reorder the terms: 56 + -8t + -7(1 + 2t) = -17 56 + -8t + (1 * -7 + 2t * -7) = -17 56 + -8t + (-7 + -14t) = -17 Reorder the terms: 56 + -7 + -8t + -14t = -17 Combine like terms: 56 + -7 = 49 49 + -8t + -14t = -17 Combine like terms: -8t + -14t = -22t 49 + -22t = -17 Solving 49 + -22t = -17 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + -22t = -17 + -49 Combine like terms: 49 + -49 = 0 0 + -22t = -17 + -49 -22t = -17 + -49 Combine like terms: -17 + -49 = -66 -22t = -66 Divide each side by '-22'. t = 3 Simplifying t = 3
| 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x | | -(3x-2)-(x+4)=-(2x-2)-(2x+4) | | 10+30b=-2 | | 11520=32x^2+64x | | 9x-4x-15=-35 |